PENGARUH LABA AKUNTANSI DAN TINGKAT SUKU BUNGA PADA RETURN SAHAM - Simona, Lidya Irene (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to analyze the influence of Accounting income and interest rate to the LQ45 companiesâ stock return in Indonesia Stock Exchange. The data is using accounting income data, BI rate, andstock return from 2010 â 2012. The selection of samples is carried out by using purposive sampling and the datacollection technique is gained from the publication of companyâs performance summary at Indonesia StockExchange website and reliable websites of economic and business data. The data examination is performed byusing multiple linear regressions and SPSS software as analysis instrument. The partial result of betweenaccounting income and interest rate shows that accounting income variable has no significant influence to theLQ 45 companiesâ stock return in Indonesia Stock Exchange while interest rate variable has significant positiveinfluence to the LQ 45 companiesâ stock return in Indonesia Stock Exchange. Simultaneously the result ofresearch shows that accounting income and interest rate variable have significant influence to the LQ 45companiesâ stock return in Indonesia Stock Return.Keywords : Accounting Income, Interest Rate, Stock Return